ASEAN COMMUNITY: MANAGING NATURAL RESOURCES FOR SUSTAINABLE DEVELOPMENT - Lengga Pradipta (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2015)
This article briefly reviews the ASEAN community and how they associated with the natural resources management issues especially in utilizing the resources to enhance the sustainable economic development. It does not address fundamental questions about development in a broad sense, but be more specific on managing the natural resources for the people’s welfare. This article strives to develop a new standard for managing natural resources, which addressed the significant inter-related and inter-connected in all areas such as political, institutional, natural resources management, human rights, economic and governance. The standard therefore considers how problems are defined and how strategy is formulated to deal with the natural resources problems. Furthermore, since the world pays attention to ASEAN as a promising model of economic development, the latter has to ensure the sustainability of environmental and natural resources in the region, because it is not only about achieving the economic milestone, but also to protect natural resources. Overall, managing natural resources is not merely the responsibility of ASEAN community, but it also needs the active involvement of various governments and policy-makers.Keywords: ASEAN Community, Natural Resources Management, Sustainable Development